Gastropod Community Structure in Ecosystem Lamun Village Lihunu North Minahasa Regency North Sulawesi Province - Manaida, Frendi; Lalita, Jans D.; Salaki, Meiske S.; Lumingas, Lawrence J. L.; Menajang, Febry S. I.; Ompi, Medy (Jurnal Ilmiah Platax, 2022)
The research was conducted in the seagrass ecosystem of Lihunu Village, East Likupang Subdistrict, North Minahasa Regency, and North Sulawesi Province.  The area is one of the coastal areas in North Sulawesi that lack information about gastropod resources. Therefore, the main reason for conducting research is to find out the presence of gastropods in the area.  The purpose of the study was to know the types of gastropods and to know the structure of communities through species density, relative density, diversity, and dominance. Sampling is done using the quadratic transect technique measuring 50 x 50 cm.  Quadrate used 50 cm x 50 cm, then converted to square meters to 0,25 m2. The density of the species is 4,80 Ind/m2.  The relative density value of the species with the highest percentage is in Euplica scripta Species with a value of 14,44% and the species with the lowest percentage value, namely Cymbiola vespertilio Species with a value of 0,56%.  Diversity index values in 3 transects fall under the high criteria. Transect 1 is H'= 5.30, transect 2 is H'= 4,18 and transect 3 is H' = 3,95. And the highest dominance value in Euplica scripta Species with a value of C = 0,48.  The water area of Lihunu Village of North Minahasa Regency has an average temperature of 30 ° C.  Salinity is obtained with an average of 30‰. The degree of acidity (pH) obtained is 8.Keywords: Gastropod; Community Structure; Lihunu.AbstrakPenelitian dilakukan di ekosistem lamun perairan Desa Lihunu, Kecamatan Likupang Timur, Kabupaten Minahasa Utara, Provinsi Sulawesi Utara. Daerah tersebut menjadi salah satu daerah pesisir di Sulawesi Utara yang kekurangan informasi mengenai sumberdaya gastropoda. Oleh karena itu, yang menjadi alasan utama melakukan penelitian adalah untuk mengetahui keberadaan gastropoda di daerah tersebut. Tujuan dari penelitian ini yaitu mengetahui jenis-jenis gastropoda serta mengetahui struktur komunitas melalui: Kepadatan spesies, kepadatan relatif, keanekaragaman, dan dominansi. Pengambilan sampel dilakukan dengan menggunakan teknik transek kuadrat berukuran 50 x 50 cm. Kuadrat yang dipakai 50 cm x 50 cm, kemudian dikonversikan ke meter persegi menjadi 0,25 m2. Nilai kepadatan spesies yaitu 4.80 Ind/m2. Nilai kepadatan relatif jenis dengan persentase tertinggi terdapat pada Spesies Euplica scripta dengan nilai 14.44% dan spesies dengan nilai persentase terendah yaitu Spesies Cymbiola vespertilio dengan nilai sebesar 0,56%. Nilai indeks keanekaragaman di 3 transek masuk dalam kriteria tinggi. Transek 1 yaitu H’= 5,30 ,pada transek 2 yaitu H’= 4,18 dan transek 3 yaitu H’ = 3,95. Dan nilai dominansi tertinggi pada Spesies Euplica scripta dengan nilai C = 0.48. Daerah perairan Desa Lihunu Kabupaten Minahasa Utara memiliki rata-rata suhu 30°C. Salintas yang diperoleh dengan rata-rata 30‰. Derajat keasaman (pH) yang diperoleh yaitu 8.Kata kunci :Gastropoda; Struktur Komunitas; Lihunu.